Protein reviews. Volume 18 - Atassi, M. Zouhair (Springer, 2020)
Mechanism of channel gating and regulation of the activity of calcium-activated chloride channel ANO1 -- Structure and function of the two-component cytotoxins of Staphylococcus aureus -- Membrane Fusion and Infection of the Influenza Hemagglutinin -- Deciphering the impact of arrhythmogenic mutations through the structural determination of the L-type voltage-gated calcium channel -- Histone post-translational modifications and nucleosome organisation in transcriptional regulation: Some open questions -- Regulation of the extracellular SERPINA5 (protein C inhibitor) penetration through cellular membranes -- Coding of Class I and II aminoacyl-tRNA synthetases -- Regulation of nephrin phosphorylation in diabetes and chronic kidney injury -- The Structure-Forming Juncture in Oxidative Protein Folding: What happens in the ER? -- Polyspecificity of Anti-Lipid A Antibodies and its Relevance the Development of Autoimmunity.